2016
DOI: 10.1007/s40291-016-0204-5
|View full text |Cite
|
Sign up to set email alerts
|

FGFR Family Members Protein Expression as Prognostic Markers in Oral Cavity and Oropharyngeal Squamous Cell Carcinoma

Abstract: IntroductionFibroblast growth factor receptor family member proteins (FGFR1–4) have been identified as promising novel therapeutic targets and prognostic markers in a wide spectrum of solid tumors. The present study investigates the expression and prognostic value of four FGFR family member proteins in a large multicenter oral cavity squamous cell carcinoma (OCSCC) and oropharyngeal squamous cell carcinoma (OPSCC) cohort.MethodsProtein expression of FGFR1–4 was determined by immunohistochemistry on tissue micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…However, FGFR1 protein overexpression showed no effect on survival outcomes. Previous studies have shown a disagreement with prognostic values of FGFR1 overexpression in HNSCC, probably owing to the use of different FGFR1 overexpression criteria, anti-FGFR1 antibodies, and cohorts with different anatomical locations [13,17,37]. FGFR1 demonstrated strong and diffused expression in poorly differentiated SCC, while normal, dysplastic squamous epithelium, or well differentiated SCC exhibited weak to moderate expression patterns.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, FGFR1 protein overexpression showed no effect on survival outcomes. Previous studies have shown a disagreement with prognostic values of FGFR1 overexpression in HNSCC, probably owing to the use of different FGFR1 overexpression criteria, anti-FGFR1 antibodies, and cohorts with different anatomical locations [13,17,37]. FGFR1 demonstrated strong and diffused expression in poorly differentiated SCC, while normal, dysplastic squamous epithelium, or well differentiated SCC exhibited weak to moderate expression patterns.…”
Section: Discussionmentioning
confidence: 91%
“…These aberrant FGFR1 alterations, in general, lead to gain-offunction characteristics and constitutively activate the downstream RAS/mitogen-activated protein kinase (MAPK), PI3K/protein kinase B (AKT), and Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signaling pathways [11]. In previous studies of HNSCC, FGFR1 amplification has been reported in 3 to 17% of cases, and FGFR1 protein overexpression has been identified in about 11-82% of cases [12][13][14][15][16][17][18]. However, they presented conflicting results for FGFR1 as a prognostic biomarker.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGFR1 gene amplification is considered a prognostic marker in HNSCC and might be a potential therapeutic target for patients with oral cancer in the future. Although nonselective tyrosine kinase inhibitors cause several adverse effects, selective FGFR‐inhibitors have already shown therapeutic value in HNSCC cell lines …”
Section: Fgf‐2/fgfr‐1 Expression In Oral Squamous Cell Carcinoma (Oscc)mentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC)encompassing the oral squamous cell carcinoma, oropharyngeal squamous cell carcinoma, hypopharyngeal squamous cell carcinoma and laryngeal squamous cell carcinoma is the sixth most common cancer worldwide, accounting for approximately 1-2% of all cancer deaths, with about 600,000 detection of new cases each year globally [1,2,3].The treatment of patients at the early stage is relatively successful, but the overall survival rate of recurrent or metastatic HNSCC remains low and has barely seen any improvements in their survival for decades [4,5]. Although the past three decades have seen several improvements in the diagnostic tools and treatment regimens, the overall survival rate for the advanced (stage Ⅲ-Ⅳ) head and neck squamous cell carcinoma (HNSCC) is only 65% [6,7]. The current standard of care for such patients are surgery along with radiation and chemotherapy, but these have not significantly improved the 5year survival of the HNSCC patients.…”
mentioning
confidence: 99%